(3OhGhjf GdTYQGA GdSJI GdLGgdjjfs - (3GdGYde GdTfbQj , jhSa Hf SdjeGf Hf YjSi GdTfJeQj GdCfOdSj, CHh GdMLGL,J (B476 (3g` s
(3ChdgG (B:s
(3bGd (B((3GeQD GdbjS(B): (3baGfHc ef PcQi MHjH hefRd HSbW Gddhi Hjf GdONhd aMhed s
(3BNQgG (B:s
(3ef TYQ YfJQI bhdg(B: (3hcGf aJi GdgjLGA jMei PeGQgG hjVQH YfO GdcQ cd HfGf s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3hGdhQbI GdChdi hGdCNjQI HNW eZQHj MOjKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B233 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B302s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs